2018
DOI: 10.18287/2412-6179-2018-42-5-898-903
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of information from multiple Kinect sensors for 3D object reconstruction

Abstract: In this paper, we estimate the accuracy of 3D object reconstruction using multiple Kinect sensors. First, we discuss the calibration of multiple Kinect sensors, and provide an analysis of the accuracy and resolution of the depth data. Next, the precision of coordinate mapping between sensors data for registration of depth and color images is evaluated. We test a proposed system for 3D object reconstruction with four Kinect V2 sensors and present reconstruction accuracy results. Experiments and computer simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…More complicated applications for analysis of complex human movement sequences require to use multiple cameras to capture orthogonal views of the same subject in order to extract the motion information and assure an objective evaluation of the training progress. For example, the studies have reported the use of two [16], three [31,65,66], four [44,51], or even five [39] Kinect sensors for estimating joint positions.…”
Section: Related Workmentioning
confidence: 99%
“…More complicated applications for analysis of complex human movement sequences require to use multiple cameras to capture orthogonal views of the same subject in order to extract the motion information and assure an objective evaluation of the training progress. For example, the studies have reported the use of two [16], three [31,65,66], four [44,51], or even five [39] Kinect sensors for estimating joint positions.…”
Section: Related Workmentioning
confidence: 99%
“…Nowadays 3D high-quality model of real objects are needed in various areas such as medicine, agriculture, architecture, engineering, industrial metrology, cultural heritage preservation and restoration [1,2,3]. Accurate 3D object reconstruction is an important aspect for scene understanding, object retrieval, object tracking, object recognition, visualization and virtual maintenance [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use for three-dimensional facial reconstruction and face alignment a resampling method based on a non-rigid ICP algorithm [8][9][10][11][12][13][14][15][16][17] instead of network-based methods. First, we convert a 3D scan to the "canonical form".…”
Section: Introductionmentioning
confidence: 99%